Bio-based polycarbonate from limonene oxide and CO2 with high molecular weight, excellent thermal resistance, hardness and transparency. Issue 3 (15th September 2015) - Hauenstein, O.; Reiter, M.; Agarwal, S.; Rieger, B.; Greiner, A.
Abstract : Completely bio-based high molecular weight aliphatic poly(limonene carbonate) with excellent transparency, superior hardness compared to BPA-PC and a high T g of 130 °C. Abstract : Completely bio-based, high molecular weight (>100 kDa) poly(limonene carbonate) (PLimC) with attractive thermal (glass transition temperature, T g = 130 °C) and optical properties (transmission 94%, haze 0.75%) was prepared by coupling bio-based limonene oxide (LO) and carbon dioxide (CO2 ) using a β-diiminate zinc catalyst (bdi)Zn(OAc). The molar mass of the polymer could be controlled by changing the ratio of catalyst and monomer, keeping molar mass dispersities low. The synthesis of the LO with very high content (>85%) of trans -isomer and absence of impurities with hydroxyl functionality was also established, which was necessary to obtain a high molar mass of polymer and almost quantitative conversion of epoxide during polymerisation. The upscaled syntheses of both the monomer and the polymer (>1 kg per batch) were readily realised, suggesting an easy transfer to pilot plant scale. The polymerisation kinetics were studied suggesting a second order dependence on LO concentration, wherefrom a mechanism is proposed with an alternating insertion of LO and CO2 . The effect of chain-ends on the thermal stability of PLimC was studied with a thermal desorption unit coupled with gas chromatography-mass spectrometry (GC-MS) experiments. PLimC with thermal stability as high as 240 °C could be achieved using appropriate end-capping agents. PLimC is characterised by excellent transparency and hardness.